Estimation of spontaneous blinking main sequence in normal subjects and patients with Graves' upper eyelid retraction - Garcia, Denny M.; Barbosa, José Carlos [UNESP]; Pinto, Carolina T.; Cruz, Antonio Augusto V. (Association for Research in Vision and Ophthalmology (ARVO), 2013)
Purpose. We quantified the main sequence of spontaneous blinks in normal subjects and Graves' disease patients with upper eyelid retraction using a nonlinear and two linear models, and examined the variability of the main sequence estimated with standard linear regression for 10-minute periods of time. Methods. A total of 20 normal subjects and 12 patients had their spontaneous blinking measured with the magnetic search coil technique when watching a video during one hour. The main sequence was estimated with a power-law function, and with standard and trough the origin linear regressions. Repeated measurements ANOVA was used to test the mean sequence stability of 10-minute bins measured with standard linear regression. Results. In 95% of the sample the correlation coefficients of the main sequence ranged from 0.60 to 0.94. Homoscedasticity of the peak velocity was not verified in 20% of the subjects and 25% of the patients. The power-law function provided the best main sequence fitting for subjects and patients. The mean sequence of 10-minute bins measured with standard linear regression did not differ from the one-hour period value. For the entire period of observation and the slope obtained by standard linear regression, the main sequence of the patients was reduced significantly compared to the normal subjects. Conclusions. Standard linear regression is a valid and stable approximation for estimating the main sequence of spontaneous blinking. However, the basic assumptions of the linear regression model should be examined on an individual basis. The maximum velocity of large blinks is slower in Graves' disease patients than in normal subjects. © 2013 The Association for Research in Vision and Ophthalmology, Inc.
Keywords: adult; blinking; clinical article; controlled study; endocrine ophthalmopathy; eyelid retraction; female; human; linear regression analysis; magnetic field; male; mathematical model; nonlinear regression analysis; priority journal; upper eyelid; velocity; Adult; Analysis of Variance; Blinking; Eyelids; Female; Graves Ophthalmopathy; Humans; Male; Video Recording